The potential of bundle innovation in closing gender yield gaps - Ziblila, Rashida; Abdul Rahman, Nurudeen; Ndibalema, Gloriana (CGIAR System Organization, 2024)
Women in agriculture contribute significantly towards sustaining rural livelihoods and achieving food and nutrition security. According to FAO, women play an important role in ensuring world food security contributing to up 43% of agricultural labor force in developing countries. However, they are faced discriminatory gendered social norms which limit their access to and control over production resources (land, labor, seed, fertilizer, livestock and finance) and improved agricultural technologies. To address these challenges, women farmers in Lungo community of Upper East Region of Ghana are practicing bundle innovation of mechanized maize seed with basal NPK fertilizer at planting and leaf stripping for improved maize grain yield and quality feed for livestock production.